Myocarditis in Crohn's disease: a case report. Issue 4 (8th July 2020) - McGrath-Cadell, Lucy; Bart, Nicole K; Lin, Linda; Ghaly, Simon; Holloway, Cameron J
Abstract: Background: Mobile valvular masses are often considered pathognomonic for infective endocarditis. We present a case of a young patient with mobile valvular masses in the context of myocarditis likely secondary to active ileal Crohn's disease. Cardiac magnetic resonance (CMR) imaging was crucial in diagnosing and monitoring our patient. Case summary: A 27-year-old woman presented with pleuritic chest pain, dyspnoea, and a 3-day history of fevers. She also reported a 2-month history of intermittent visual loss in her right eye. She had a history of histologically proven ileal Crohn's disease, diagnosed 5 months prior. She was haemodynamically unstable on presentation. Abnormalities on a transthoracic echocardiogram necessitated a transoesophageal echocardiogram. After blood cultures were sent, the patient was commenced on empirical treatment for infective endocarditis with gentamicin and flucloxacillin. Eight days after her initial presentation, all blood cultures remained negative and she was changed to empirical treatment for culture negative endocarditis with ceftriaxone and vancomycin, according to local protocol. Despite 8 days of treatment for infective endocarditis she remained febrile. A CMR was organized on Day 9 and this showed myocarditis, which changed the treatment paradigm. She responded swiftly to steroids and anti-coagulation. Discussion: In this case, echo-dense valvular lesions are not pathognomonic for infective endocarditis and a careful diagnostic process involving multi-modality imaging, including CMR, occurred to arrive at a diagnosis of myocarditis likely secondary to Crohn's disease.